(untitled) (Journal of Educational Sciences, 2025)
The rapid advancement of information and communication technologies has led to the emergence of innovative educational tools, significantly impacting foreign language learning. This study explores the effectiveness of Web 2.0 and Web 3.0 technologies in enhancing language acquisition at L.N. Gumilyov Eurasian National University over a four-month period. University students participated in interactive sessions using a variety of digital tools, including blogs, wikis, social media platforms, and semantic web technologies, which facilitated both direct and personal interaction. Quantitative data were gathered through a comprehensive 37-item questionnaire and detailed blog reflections, providing insights into students’ experiences, interaction dynamics, and feedback on the technological tools used. The findings reveal that Web 2.0 and Web 3.0 tools, with their ability to support semantic networks, significantly enrich the learning experience compared to traditional methods, leading to improved language skills. The study underscores the necessity for continuous pedagogical adaptation to effectively incorporate these technologies, thereby promoting principles of lifelong learning. 100 students of the L.N. Gumilyov Eurasian National University took part in the survey.The practical significance of this research lies in its potential to inform educational strategies, fostering a more interactive and personalized learning environment. Future investigations can be devoted to adaptive network communities to further refine and enhance educational practices in the digital age. Key words: Web 2.0, Web 3.0, foreign language learning, educational technology, network communities, higher education, semantic web, interactive learning.